Wild Wonder Animals Explorers - Zulkefli, Nuriman Maisarah; Hussien, Nur Syahela (Journal of Computing Technologies and Creative Content, 2025)
Animal Explorers project is an interactive Augmented Reality (AR) storybook designed to educate and engage children aged between 4 to 8 years on the subject of wildlife and environmental conservation. The storybook is enriched with 3D animal models, animations, and immersive auditory elements, offering a captivating learning experience that encourages curiosity about nature. Developed using Unity, Blender, and Adobe Illustrator, the project merges narrative storytelling with interactive AR content to introduce children to the concepts of biodiversity, ecosystems, and the importance of conservation. By integrating storytelling with AR, this project not only enhances traditional learning but also aligns with educational goals related to STEM (Science, Technology, Engineering, and Mathematics) and environmental awareness. The research methodology adopts the ADDIE model, guiding the project through structured phases of analysis, design, development, implementation, and evaluation. The goal of this study is to create an impactful learning tool that fosters environmental consciousness in young learners while promoting active engagement through technology.